Clinico-Pathological Features, Management, and Outcome in Patients with Carcinoma of Oral Cavity (International Journal of Food and Nutritional Sciences, 2022)
Background: Oral carcinoma ranks 8th commonest carcinoma in the world.(1) In a developing country like India, it becomes the commonest cancers out of all by a gross margin of up to 40% cases annually among all type of cancers. Multiple risk factors and varying trends in the age and subsite demands active research in the field of oral carcinoma. Newer management modalities provide better prognosis than previous treatment protocols. Keeping this in mind, we have conducted and studied extensively on the age, sex, risk factors, subsites, investigations, management, and outcomes in case of carcinoma of oral cavity.Aims: To evaluate the clinicopathological features, management, and outcome in carcinoma of oral cavity.Materials and methods: A cross sectional observational study conducted in Santosh medical college during July 2021- June 2022 on 32 patients diagnosed with squamous cell carcinoma of oral cavity.Results: Most of the patients were in the middle aged less than 5th decade with male predominance. Chewable tobacco had the highest association out of all risk factors in all the cases. Majority of the patients presented with ulcer and buccal mucosa being the commonest subsite of occurrence and having premalignant lesion of leucoplakia as the usual presentation. Majority of cases were presented in the advanced stageConclusion: Oral cavity carcinoma invites serious threat to the Indian population as with the influence of tobacco predominantly chewing and alcohol. Serious association with lower socioeconomic status suggest better habitats and employment, education and awareness in the field of oral cavity carcinoma and their outcomes.